Synthesis and photocatalytic properties of CeVO4 nanoparticles under UV irradiation - P. Intaphong (2018)
© 2015, Inst Materials Physics. All rights reserved. In this research, CeVO 4 nanoparticles have been successfully synthesized by hydrothermal reaction. The as-synthesized CeVO 4 nanoparticles were characterized by X-ray powder diffraction (XRD), Raman spectroscopy, Fourier transform infrared (FTIR) spectrophotometry and scanning electron microscopy (SEM). The photocatalytic activity of the as-synthesized CeVO 4 nanoparticles was evaluated via the photodegradation of methylene blue (MB) under UV irradiation. In this research, the tetragonal CeVO 4 nanoparticles with the particle size less than 100 nm were detected. The V–O stretching and bending in VO 4 3– tetrahedrons were detected by FTIR and Raman spectrometry. The photocatalysis of MB by CeVO 4 nanoparticles exhibited the decolorization efficiency of 80 % within 300 min.